Role of Vitamin D at Urinary Level as a Potential Biomarker in Diabetic Nephropathy among Pakistani Population - Muhammad Shahzad Hafeez, Abdul Hayee Phulpoto, Nauman Rafi Rajput, Alisha Shaukat, Arooj Fatima, Hizbullah (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Diabetic nephropathy (DN) is a microvascular complication of diabetes mellitus and it’s a leading cause of end-stage renal disease (ESRD) worldwide. Objectives: The main objective of the study is to find the role of Vitamin D at urinary level as a new biomarker in analysis of diabetic nephropathy in Pakistani population. Methodology: This cross-sectional study was conducted at Sahara Medical College Narowal from February 2022 to March 2023. Data were collected according to inclusion and exclusion criteria from 550 patients suffering from DN. Demographic and clinical data were collected from each patient through systematically designed performa which contain questions related to duration of disease, history, medication, glycemic control and all other related data. Urinary sample were drawn from every patient to measure the levels of Vit-D in urine. Results: Data were collected from 550 confirmed patients of DM. Mean age of the participants was 55.3 ± 9.7 years. There were 302 (55%) male population and 248 (45%) female population in the study. Mean duration of DM were 9.89±2.34 years and mean levels of HbA1c was 8.5 ± 1.2 (%). There were 50 patients who had urinary Vit-D levels were <10ng/mL, 200 with 10-20ng/mL, 250 with 20-30ng/ml and 50 patients had >30ng/mL. In type I DM patients mean levels of urinary Vit-D was 18.5 ± 4.0 ng/mL and in type II 21.0 ± 5.0 ng/ml. Patients with eGFR <60 have 19.0 ± 4.0ng/mL, 60-90 with 23.0 ± 5.0ng/mL and >90 with 25.0 ± 5.0ng/mL urinary vit-D levels. Conclusion: It is concluded that Vit-D levels shows an inverse relationship with albumin to creatinine ratio in diabetic nephropathy patients which suggest strong reno-protective effect against DN. Urinary Vit-D levels is considered to be a potential biomarker in the assessment of DN and renal functions in Pakistani population suffering from DM. Keywords: Patients, Vit-D, DM, Population, Urinary, Creatinin.